Cerebellar Involvement in Dengue Fever - Rupak Chatterjee; Shatavisa Mukherjee (International Journal of Advanced Medical and Health Research)
Dengue fever is a common and important arboviral infection prevalent in tropical countries, contributing to significant morbidity and mortality. The clinical spectrum of dengue fever ranges from simple febrile illness to life-threatening complications such as dengue hemorrhagic fever and dengue shock syndrome. Among the many unusual manifestations of this fever, a rare entity is its cerebellar involvement. This report aims to highlight this uncommon presentation.